2001
DOI: 10.1128/jb.183.4.1346-1358.2001
|View full text |Cite
|
Sign up to set email alerts
|

Subset of Hybrid Eukaryotic Proteins Is Exported by the Type I Secretion System of Erwinia chrysanthemi

Abstract: Erwinia chrysanthemi exports degradative enzymes by using a type I protein secretion system. The proteases secreted by this system lack an N-terminal signal peptide but contain a C-terminal secretion signal. To explore the substrate specificity of this system, we have expressed the E. chrysanthemi transporter system (prtDEF genes) in Escherichia coli and tested the ability of this ABC transporter to export hybrid proteins carrying C-terminal fragments of E. chrysanthemi protease B. The C terminus contains six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 67 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…First, based on the apparent affinities and activities of the RTX and AP proteins, AP would remain unfolded or destabilized within the cell. In an extended conformation, transport could occur without the need for a cellular unfoldase activity because secretion is thought to occur post-translationally and require an unfolded polypeptide substrate (21,27). Maintaining the cytosolic AP in an unfolded conformation would also limit unwanted enzymatic activity prior to secretion.…”
Section: Discussionmentioning
confidence: 99%
“…First, based on the apparent affinities and activities of the RTX and AP proteins, AP would remain unfolded or destabilized within the cell. In an extended conformation, transport could occur without the need for a cellular unfoldase activity because secretion is thought to occur post-translationally and require an unfolded polypeptide substrate (21,27). Maintaining the cytosolic AP in an unfolded conformation would also limit unwanted enzymatic activity prior to secretion.…”
Section: Discussionmentioning
confidence: 99%
“…'Natural' passenger proteins of the T1SS do not usually contain any cysteine residue, or in some cases, contain only one cysteine residue, indicating that these proteins do not have any intramolecular disulfide bond. A study on secretion of hybrid eukaryotic proteins fused with C domain of E. chrysanthemi protease showed that E. chrysanthemi T1SS can only secrete proteins that do not have any intramolecular disulfide bond [79]. Another report, however, showed that E. coli alkaline phosphatase, a dimeric periplasmic protein with two intramolecular disulfide bonds (four cysteine residues in one monomer), can be secreted extracellularly when it is fused with the C-terminal secretion signal of α-hemolysin [80].…”
Section: Passenger Proteins Of the T1ssmentioning
confidence: 95%
“…AF083061) [59]. In this review, we use the latter as the correct sequence, since the first sequence contains nine cysteine residues, a feature uncommon in proteins secreted via the T1SS [79].…”
Section: Amino Acid Sequences Of Family I3 Lipasesmentioning
confidence: 99%
“…However, previous studies pointed out that additional domains must be involved in the interaction with the secretion complex. First, efficient secretion of heterologous proteins fused to E. coli HlyA or E. chrysanthemi PrtB requires C-terminal fragments much larger than the minimal secretion signals (20,25,33). Second, hemophore HasA(1-174) without its C-terminal signal retains its capacity to interact with HasD and induce the assembly of the tripartite complex (7).…”
Section: Discussionmentioning
confidence: 99%